Estudo da diversidade microbiana no tratamento de efluentes gordurosos em reator anaeróbio compartimentado - Rojas, Karina Biasetto (2016)
An Anaerobic Baffled reactor, with five chambers, with high organic matter removal efficiencies (around 90%), fed with synthetic substrate simulating dairy wastewaters, was used in the present study in order to follow the microbial community changes along its operational period. The modifications were followed in order to access the sludge capability of mineralization of long chain fat acids (LCFA). The reactor was operated for 270 days during which, was subjected to rising organic loading rates, due to hydraulic detention time diminution (from 24 to 72 hours). Three different samples were dropped, one on the 50th day, with HDT of 72 hours over 25°C, a second sample in the 150th day with HDT of 72 hours but now with temperature controlled with termostate at 37°C and the last sample in day 27 with HDT of 24 hours at 37°C. Three periods were elected for sludge collection, when the samples were subjected to PCR/DGGE with specific primers for Archaea and Bacteria Domains, allowing the microbial community diversity access. The study was complemented with specific methanogenic activity assays, conducted in the inoculum samples and in the samples form the reactor after 270 days of operation. The microbial community presented important modifications along the reactor operation, being the more evident, the presented by de Bacteria Domain. The sludge from the first chamber, despite have been subjected to the higher LCFA loadings, showed the higher SMA values. The study allowed the verification of the adaptation capability of the anaerobic sludge, inferring that the observed modifications were important maintain the high organic matter efficiencies observed in the system.